2005
DOI: 10.1002/clc.4960281208
|View full text |Cite
|
Sign up to set email alerts
|

Increase in aortic pulse wave velocity is associated with abnormal postprandial triglyceride response

Abstract: SummaryBackground: Aortic pulse wave velocity (aPWV), an index of aortic distensibility, and postprandial hypertriglyceridemia are recognized as independent cardiovascular risk factors.Hypothesis: The aim of this study was to evaluate the relationship between postprandial hypertriglyceridemia and changes in aPWV.Methods: We prospectively studied 45 patients (mean age 48 [14] years, 28.9% men), who were submitted to a standardized fat meal (FM) test. According to their triglyceride (TG) levels 2, 4, 6, and 8 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
0
5
0
1
Order By: Relevance
“…Additionally, in 45 patients who underwent a standardized fatty meal test and whose triglycerides levels were subsequently measured after 2, 4, 6 and 8 hours, it was shown that high post-challenge triglycerides correlated positively with an increase in aortic pulse wave velocity (aPWV) 6 hours after the fatty meal consumption and, specifically, a 0.88 m/s rise of aPWVA was found for a 100mg/dl increase in triglycerides. 80 Waist circumference, which is an index of central obesity, constitutes a well-recognized cardiovascular risk factor in hypertensive patients 55 and has also been reported to be associated with such conditions as, inter alia, idiopathic portal vein thrombosis, 81 asthma in children and adolescents and uncontrolled asthma in women, 82,83 non-alcoholic liver disease 84 and dementia. 85 Oka et al conducted a study including 1,505 men and 798 women who were not taking medications for diabetes or dyslipidemia.…”
Section: Nordestgaard Et Al 2007mentioning
confidence: 99%
“…Additionally, in 45 patients who underwent a standardized fatty meal test and whose triglycerides levels were subsequently measured after 2, 4, 6 and 8 hours, it was shown that high post-challenge triglycerides correlated positively with an increase in aortic pulse wave velocity (aPWV) 6 hours after the fatty meal consumption and, specifically, a 0.88 m/s rise of aPWVA was found for a 100mg/dl increase in triglycerides. 80 Waist circumference, which is an index of central obesity, constitutes a well-recognized cardiovascular risk factor in hypertensive patients 55 and has also been reported to be associated with such conditions as, inter alia, idiopathic portal vein thrombosis, 81 asthma in children and adolescents and uncontrolled asthma in women, 82,83 non-alcoholic liver disease 84 and dementia. 85 Oka et al conducted a study including 1,505 men and 798 women who were not taking medications for diabetes or dyslipidemia.…”
Section: Nordestgaard Et Al 2007mentioning
confidence: 99%
“…On the other hand, an "acute" vascular response to blood lipid changes may not be noticeable for some hours. 36 …”
Section: Exercise-central Bpmentioning
confidence: 99%
“…To which degree the small difference in plasma triglycerides can influence the PWV measurements is unknown. Ingestion of a high‐fat meal increased aortic PWV in one study (Daskalova et al ., ), but this finding could not be reproduced in another investigation (Frimodt‐Moller et al ., ).…”
Section: Discussionmentioning
confidence: 74%